Goods Procurement Audit System Information At PT. Global Satria Aji - Maya Pratiwi; Narti Narti (Paradigma - Jurnal Komputer dan Informatika, 2023)
As an effort to realize ideal information for companies, the implementation of reliable information technology governance is needed by companies. This study aims to audit the application of information technology governance of the goods procurement system at PT. Global Satria Aji, because the company PT. Satria Aji Global wants to check profit or loss and also wants to minimize losses related to the goods procurement system.  The problem that is often experienced by companies is a system that is deemed unable to accommodate all the data needed when incoming data increases. This study uses the COBIT 5 framework using the EDM01, APO01, APO02, APO07, DSS01 and MEA01 process domains. The calculation of the average maturity level of the six domains used is 1.58 in decimal numbers or 158% in percent. In the study it was found that the biggest discrepancy occurred in the APO01 domain where the difference between the expected conditions and the conditions that occurred reached 2.04. The recommended improvement is to provide a consistent management approach so as to enable corporate governance requirements to be met.